Effect of promoters on the HDS activity of alumina-supported Co–Mo sulfide catalysts. Issue 121 (20th November 2015) - Wang, Xilong; Fang, He; Zhao, Zhen; Duan, Aijun; Xu, Chunming; Chen, Zhentao; Zhang, Minghui; Du, Peng; Song, Shaotong; Zheng, Peng; Chi, Kebin
Abstract : Supported MoCo/δ-Al2 O3 catalysts promoted by different organic and inorganic cobalt salts were synthesized by incipient-wetness impregnation. The HDS activities of the catalysts increased in the order MoCo-A/δ < MoCo-N/δ < MoCo-D/δ < MoCo-S/δ. Abstract : A series of CoMo/δ-Al2 O3 catalysts promoted by different organic and inorganic cobalt salts were successfully prepared using low-cost δ-Al2 O3 as a support through a two-step incipient-wetness impregnation method. The obtained catalysts were indicated as MoCo-N/δ, MoCo-S/δ, MoCo-A/δ and MoCo-D/δ, in which N, S, A, D, and δ represent cobalt nitrate, cobalt sulfate, cobalt acetate, cobalt diacetylmethane, and δ-Al2 O3, respectively. The as-synthesized catalysts were introduced to the hydrodesulfurization (HDS) process of fluid catalytic cracking (FCC) diesel, in a fixed-bed reactor. The oxidized catalysts and the corresponding sulfurized catalysts for HDS were characterized by UV-vis, Raman, X-ray diffraction, TPR, and XPS techniques. The catalytic activities followed the order of MoCo-A/δ < MoCo-N/δ < MoCo-D/δ < MoCo-S/δ. These catalytic results could be ascribed to the introduction of different cobalt salts decreasing the metal-support interaction (MSI), and led to the formation of easily reduced Mo species, which were the precursors to form more active sites that could enhance the HDS activity of the catalysts. The highest activity shown by the MoCo-S/δ catalyst could be ascribed to its (1) higher metal dispersion, (2) lower Mo reduction temperature, and (3) higher sulfurization degree. As a result, the excellent catalytic performance could be attributed to its outstanding promoter effect.